MANGROVE PLANTING TRAINING IN KAMPOENG KEPITING TUBAN VILLAGE, KUTA SUB-DISTRICT, BADUNG DISTRICT, BALI - Ananda Putra, I Gusti Agung (Pusat Riset dan Inovasi Nasional, 2023)
Tuban Village is one of the villages in Badung Regency that has the potential of coastal areas that are utilized by the community for various purposes. The high utilization of coastal areas has led to the conversion of mangrove land for various purposes, resulting in damage in the form of abrasion in several places, pollution due to industrial activities, households and aquaculture activities. Therefore, mangrove forest rehabilitation program is considered as one of the important recommendations in order to restore the condition of mangrove ecosystem in this region. The training consisted of a group of Nature Lovers Students (Mapala) which included the provision of training and socialization in the field on the introduction of mangrove tree species and characteristics and mangrove tree planting techniques in theory and application of the theory that has been obtained in the form of collecting and processing mangrove trees to be used as seeds and planting practices. The results of the training showed that all participants understood the material presented. This can be seen from the way participants apply the theory obtained by direct practice in the field.